2020
DOI: 10.3390/en13164256
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Hydrodynamic Disintegrator Adjusted to Agricultural Substrates Pre-treatment Aimed at Methane Production Intensification—CFD Modelling and Batch Tests

Abstract: The study objective was to adjust the hydrodynamic disintegrator dedicated to sewage sludge pre-treatment (HDS) to work with agricultural substrate. This involved the development and implementation of a mathematical model of flow via the device’s domain. An innovative disintegrator (HAD—hydrodynamic disintegrator for agriculture) was designed, built, and tested based on the obtained results. The main improvements to the HDS include the implementation of shredding knives in order to overcome clogging by crushed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Taking into consideration the above-mentioned facts, the most widespread is the application of the following substrates: organic fraction of municipal solid waste (OFMSW); fat, oil, and grease wastes (FOG); various agro-industrial by-products (e.g., fruit and vegetable waste, glycerol and slaughterhouse wastes) [52,53]. Among the mentioned substrates, the use of wastes characterized by significant fat content is of great interest.…”
Section: Biogas Production From Sewage Sludge In a Wastewater Treatment Plantmentioning
confidence: 99%
“…Taking into consideration the above-mentioned facts, the most widespread is the application of the following substrates: organic fraction of municipal solid waste (OFMSW); fat, oil, and grease wastes (FOG); various agro-industrial by-products (e.g., fruit and vegetable waste, glycerol and slaughterhouse wastes) [52,53]. Among the mentioned substrates, the use of wastes characterized by significant fat content is of great interest.…”
Section: Biogas Production From Sewage Sludge In a Wastewater Treatment Plantmentioning
confidence: 99%
“…Several different cavitator designs have been successfully employed for advanced oxidation of dissolved organic compounds (a review provided in [1] , [6] , [7] ) and disinfection (a review provided in [2] , [8] ) of WW. These include orifice plates [9] , [10] , venturi tubes [10] , [11] , vortex cavitation [12] , and rotating devices [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] that will be hereinafter referred to as rotational generators of hydrodynamic cavitation (RGHC).…”
Section: Introductionmentioning
confidence: 99%
“…This, on the other hand, comes at the expense of a greater complexity of internal geometry and cavitation mechanism as opposed to fixed-geometry cavitators. Several different RGHC designs have been developed in the recent years, including dimpled rotors [14] , [15] , [18] , [19] , [21] , [23] vaned rotor–stator devices [20] , serrated discs [16] , [17] , [25] , [26] , [27] , and pinned discs [22] . Dimpled rotors have been proven effective in sludge solubilization [3] , [15] , destruction of cyanobacteria [18] and in esterification of vegetable oil [23] but are limited by relatively low liquid throughputs and somewhat modest COD removal performance.…”
Section: Introductionmentioning
confidence: 99%
“…US disintegration is often compared to hydrodynamic disintegration (HD), which is reported to have a lower energy consumption compared to US disintegration [32,33]. Zubrowska-Sudoł et al (2020) reported an sCOD increase of 6.5-185% at a HD energy dose of 210 kJ/L for maize silage [33], while in this study, the manure digestate of 22 days ultrasonicated with 3000 kJ/kg TS or 213 kJ/L resulted in an increase in the sCOD of 41%.…”
Section: Effect Of Digestate Age On Us Disintegration Efficiencymentioning
confidence: 99%
“…US disintegration is often compared to hydrodynamic disintegration (HD), which is reported to have a lower energy consumption compared to US disintegration [32,33]. Zubrowska-Sudoł et al (2020) reported an sCOD increase of 6.5-185% at a HD energy dose of 210 kJ/L for maize silage [33], while in this study, the manure digestate of 22 days ultrasonicated with 3000 kJ/kg TS or 213 kJ/L resulted in an increase in the sCOD of 41%. The obtained sCOD increases in this study are in the range of HD pre-treatment results; however, to the best of the authors' knowledge, no study has yet investigated the effect of HD disintegration on the digestate of an anaerobic digester.…”
Section: Effect Of Digestate Age On Us Disintegration Efficiencymentioning
confidence: 99%